Prolonged Honeymoon Period in a Thai Patient with Adult-Onset Type 1 Diabetes Mellitus. (2nd September 2021) - Thewjitcharoen, Yotsapon; Wanothayaroj, Ekgaluck; Jaita, Haruethai; Nakasatien, Soontaree; Butadej, Siriwan; Khurana, Ishant; Maxwell, Scott; El-Osta, Assam; Chatchomchuan, Waralee; Krittiyawong, Sirinate; Himathongkam, Thep
Abstract : Context . The "honeymoon" phase among people with type 1 diabetes mellitus (T1DM) refers to the period (mostly less than 1 year) in which beta-cells remain functional and are able to produce insulin to maintain good glycemic control shortly following the development of diabetes. This phenomenon is still not completely understood. Previous studies have shown that the absence of diabetic ketoacidosis (DKA) at initial presentation, short duration of symptoms, older age at presentation, and strenuous exercise could be potential factors that influence the honeymoon phase. Objective . To describe a usual case of adult-onset T1DM with prolonged honeymoon period for more than 5 years. Methods . Repeated mixed meal stimulation tests for a period of 6–12 months together with monitoring pancreatic autoantibodies and laboratory data were followed following the onset of diagnosis. Results . We report a 24-year-old Thai patient with T1DM with sustained remission without antidiabetic medication for more than 5 years while maintaining low-carbohydrate intake and regular exercise. Repeated mixed meal stimulation tests for a period of 6–12 months revealed preserved beta-cell functions. Interestingly, repeated pancreatic autoantibodies at 5 years after diagnosis still showed positive anti-GAD, anti-IA2, and anti-ZnT8. Conclusion . Restored beta-cell function with complete insulin withdrawal in new-onset T1DM has been reported in very few cases with some common factors as in our patient (low-carbohydrate intake with regular exercise). Delaying autoimmune activity by reducing metabolic load in newly diagnosed T1DM might play a role in maintaining the honeymoon period and could lead to an innovative therapeutic option in new-onset T1DM.